Indonesian vs. Bribri: Striking Lexical Similarities In Two Unrelated Languages - Haakon S. Krohn (Faculty of Languages and Arts, Universitas Negeri Padang, 2021)
Despite the fact that Indonesian and Bribri belong to two different language families and are spoken on opposite sides of the world, their lexicons contain many words that are strikingly similar. In this paper I anayze the origin of three word pairs from these languages that not only sound similar, but also have almost exactly the same meaning: (1) Indonesian kulit and Bribri kuö́lit ‘skin, hide, leather, crust, shell, bark, rind, peel’, (2) Indonesian kutu and Bribri kú̱ ‘louse’, and (3) Indonesian kupu-kupu and Bribri kua’kua ‘butterfly’. The intention is not to propose any genealogical link between the Austronesian and the Chibchan language families, but rather to show how phonological, morphological and semantic properties can converge in two unrelated languages and produce this kind of eye-catching similarities.